2018
DOI: 10.1155/2018/1286216
|View full text |Cite
|
Sign up to set email alerts
|

Detection ofYersinia enterocoliticain Retail Chicken Meat, Mashhad, Iran

Abstract: Poultry meat is one of the most important sources of infection of Yersinia spp. for humans. The aim of the present study was to evaluate the incidence of Yersinia enterocolitica in chicken meat by using culture method on selective medium and confirmation by PCR assay. Also, biochemical methods were used for biotyping. A total of 100 chicken thigh meat samples were collected randomly from retail outlets in Mashhad, Iran. Samples were enriched in Peptone-Sorbitol-Bile (PSB) broth and then cultured on Cefsulodin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 27 publications
(30 reference statements)
0
14
0
4
Order By: Relevance
“…[6] could not identify Y. enterocolitica from chicken meat while Sirghani et al . [26] recorded a higher percentage (30%) from chicken meat in Iran.…”
Section: Resultsmentioning
confidence: 99%
“…[6] could not identify Y. enterocolitica from chicken meat while Sirghani et al . [26] recorded a higher percentage (30%) from chicken meat in Iran.…”
Section: Resultsmentioning
confidence: 99%
“…However, Y. enterocolitica has been frequently isolated from poultry and ready-to-eat foods [78]. A study in Iran reported a prevalence rate of Y. enterocolitica of 30% of among chicken meat samples [79]. Yersinia isolates (16%) from chicken and beef meat samples were mostly resistant to cephalotin (98%) and ampicillin (52%) [80].…”
Section: Yersinia Speciesmentioning
confidence: 99%
“…It has the potential to survive out of the mammalian host and can grow even in 4-42 °C [1]. Y. enterocolitica has been isolated in various food substances such as pork [2], beef [3], chicken meat [4], sea foods [5], vegetables [6] and dairy products [7]. It causes Yersiniosis ranging from selflimiting gastroenteritis with abdominal pain and diarrhoea to life-threatening bacteraemia, rarely.…”
Section: Introductionmentioning
confidence: 99%